Native American DNA : tribal belonging and the false promise of genetic science - TallBear, Kimberly (University of Minnesota Press, 2013)
"Because today's DNA testing seems so compelling and powerful, increasing numbers of Native Americans have begun to believe their own metaphors: "in our blood" is giving way to "in our DNA." In Native American DNA, Kim TallBear shows how Native American claims to land, resources, and sovereignty that have taken generations to ratify may be seriously- and permanently- undermined."